2016
DOI: 10.1007/s10900-016-0168-8
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Latino Nativity, Migration, and Acculturation Factors on Colonoscopy Screening

Abstract: Objective Latinos are a diverse population comprised of multiple countries of origin with varying cultural profiles. This study examines differences in colonoscopy completion across place of birth and migration-related factors in a sample of predominantly Dominican and Puerto Rican Latinos living in New York City after receiving a recommendation for colonoscopy screening and navigation services. Design The sample included 702 Latinos recruited for two cancer screening projects targeting Latinos eligible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
(40 reference statements)
4
9
0
Order By: Relevance
“…Our findings are in opposition to most of the CRC screening-only literature, which indicates lower CRC screening rates among Black Americans, primarily Spanish speaking, and bilingual Latina immigrants [ 47 , 48 ]. In respect to Latinas, our findings are consistent with Costas-Muñiz et al who found that foreign-born, Spanish-speaking, and bilingual Latinos were more likely to complete colonoscopy compared to U.S.-born or English-speaking Latinos in New York City [ 49 ]. The authors concluded that the increased availability of CRC screening in the U.S. compared to participants’ home countries may encourage screening behaviors, while medical mistrust and other healthcare experiences may reduce US-born and acculturated foreign-born Latinos’ desire to complete screening [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are in opposition to most of the CRC screening-only literature, which indicates lower CRC screening rates among Black Americans, primarily Spanish speaking, and bilingual Latina immigrants [ 47 , 48 ]. In respect to Latinas, our findings are consistent with Costas-Muñiz et al who found that foreign-born, Spanish-speaking, and bilingual Latinos were more likely to complete colonoscopy compared to U.S.-born or English-speaking Latinos in New York City [ 49 ]. The authors concluded that the increased availability of CRC screening in the U.S. compared to participants’ home countries may encourage screening behaviors, while medical mistrust and other healthcare experiences may reduce US-born and acculturated foreign-born Latinos’ desire to complete screening [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Spanish language is associated with increased completion of colonoscopy screening after provider recommendation and patient education and support. 20 Our findings for postpartum glucose tolerance testing without any patient education and support is similar to this pattern. Previous research, however, reports that Medicaid insurance, late presentation to prenatal care, and insulin use during pregnancy were positively associated with completion of postpartum glucose tolerance screening.…”
Section: Discussionsupporting
confidence: 83%
“…Although having insurance coverage does not ensure doctor visits, universal health insurance coverage and universal access to a usual source of health care would likely increase physician access to all groups to encourage screening. Although it would be optimal for physicians to recommend screening to less acculturated and uninsured Hispanics and Asians and in their own languages ( 20 , 21 ), studies suggest that physician enthusiasm and outreach with tailored or innovative strategies to educate and inform ( 22 ) may increase knowledge and intention to screen among underserved groups, such as Hispanics, Asians, the uninsured, and the less educated. Culturally tailored strategies may be particularly effective for Asians disproportionately affected by discordance in patient–provider language and gender (provider and patient being of different genders) ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%